IMPLEMENTASI BUDAYA SEKOLAH ISLAMI DALAM RANGKA PEMBINAAN KARAKTER SISWA - Laili Jumroatun; Burhanuddin Burhanuddin; Ahmad Yusuf Sobri (Universitas Negeri Malang, 2018)
Abstract: Qualitative research with casus study design is aimed to describe Islamic school culture in two schools based on Islamic schools namely MTsN 1 Tulungagung and Islamic Junior High School Al Azhaar Tulungagung. Technique of collecting data is done by interview, observation, and documentation. Data analysis was done in single case data analysis. The results of this study indicate that in the Islamic cultural school activities are in accordance with Islamic values that will assist in fostering the character of students to be Islamic character. Keywords: Islamic school culture, character building of students Abstrak: Penelitian kualitatif dengan rancangan studi kasus yang bertujuan untuk mendiskripsikan tentang budaya sekolah Islami di dua sekolah yang berbasis sekolah Islam yaitu MTsN 1 Tulungagung dan SMP Islam Al Azhaar Tulungagung. Teknik pengumpulan data dilakukan melalui wawancara, observasi, dan dokumentasi. Analisis data dilakukan dengan cara, yaitu analisis data kasus tunggal. Hasil penelitian ini menunjukkan bahwa dalam kegiatan budaya sekolah Islami sudah sesuai dengan nilai-nilai Islami yang akan membantu dalam membinaan karakter siswa menjadi karakter Islami. Kata kunci: budaya sekolah Islami, karakter siswa